2021
DOI: 10.1248/bpb.b20-01041
|View full text |Cite
|
Sign up to set email alerts
|

Detection Method of Falsified Medicines by Using a Low-Cost Raman Scattering Spectrometer Combined with Soft Independent Modeling of Class Analogy and Partial Least Squares Discriminant Analysis

Abstract: There are many reports of falsified medicines that may cause harm to patients. A rapid and simple method of identifying falsified medicines that could be used in the field is required. Although Raman scattering spectroscopy has become popular as a non-destructive analysis, few validation experiments on falsified medicines that are actually distributed on the market have been conducted. In this study, we validated a discriminant analysis using an ultra-compact, portable, and low-cost Raman scattering spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Spectral pre-processing involved the application of Savitzky-Golay smoothing and differentiation filter (second-degree polynomial and first derivative) to remove noise and baseline signals. We then performed unit-area normalization by applying Standard Normal Variate to the smoothed and differentiated signals 48 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Spectral pre-processing involved the application of Savitzky-Golay smoothing and differentiation filter (second-degree polynomial and first derivative) to remove noise and baseline signals. We then performed unit-area normalization by applying Standard Normal Variate to the smoothed and differentiated signals 48 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Both principal component analysis (PCA) [16] and hierarchical cluster analysis (HCA) [17] belong to unsupervised methods, and they can determine the identical classification by judging the spectra similarity from different bacteria species. In addition, both soft independent modeling of class analogy (SIMCA) [18] and support vector machine (SVM) [19] are supervised learning models, having the functions of training and prediction spectra data. Unlike unsupervised model, there is one point needs to be clear is that, prior to prediction, it is required to define the labels for the training classification model.…”
Section: Introductionmentioning
confidence: 99%
“…However, Vibrational spectroscopy is a preferred detection and quantification technology in the crops industry and can address some of the limitations of the aforementioned methods when combined with multivariate statistical analysis techniques (chemometrics). In particular, near-infrared (NIR) spectroscopy showed that it could accurately quantify a wide range of elements and compounds [2,8,9]. Infrared spectroscopy has showed potential as tool for the control in different environments [10], and it also demonstrated benefits for non-invasive and immediate detection, which allowed the technique to gain acceptance and a wide range of use in industries, including biomedicine and more.…”
Section: Introductionmentioning
confidence: 99%